Ecological Sex Ratios and Human Mating. Issue 2 (February 2020) - Maner, Jon K.; Ackerman, Joshua M.
Abstract : The ratio of men to women in a given ecology can have profound influences on a range of interpersonal processes, from marriage and divorce rates to risk-taking and violent crime. Here, we organize such processes into two categories – intersexual choice and intrasexual competition – representing focal effects of imbalanced sex ratios.